2014
DOI: 10.1016/j.joca.2014.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive allogeneic intraarticular injections of synovial mesenchymal stem cells promote meniscus regeneration in a porcine massive meniscus defect model

Abstract: Intraarticular injections of allogeneic synovial MSCs appeared to promote meniscus regeneration and provide protection at the medial femoral articular cartilage in a porcine massive meniscal defect model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 29 publications
3
99
0
2
Order By: Relevance
“…Several studies have demonstrated the therapeutic capacity of SMSCs. Compared with their respective controls, the quantity and quality of regenerated tissue were found significantly greater in those groups treated with SMSCs (Matsukura et al 2014;Hatsushika et al 2014).…”
Section: Discussionmentioning
confidence: 75%
“…Several studies have demonstrated the therapeutic capacity of SMSCs. Compared with their respective controls, the quantity and quality of regenerated tissue were found significantly greater in those groups treated with SMSCs (Matsukura et al 2014;Hatsushika et al 2014).…”
Section: Discussionmentioning
confidence: 75%
“…For in vitro osteogenic differentiation expanded SF cells were seeded in triplicate at a density of 1x10 4 cells/cm 2 in 8-well plates (BD Falcon Culture Slides) in the complete and Stem PRO osteogenesis medium for 21 days. Some cultures were interrupted the fi fth day to determine alkaline phosphatase (AP) activity using Alkaline Phosphatase Detection Kit (Sigma) according to manufacturer's instructions.…”
Section: In Vitro Differentiation Of the Sf Cellsmentioning
confidence: 99%
“…Neither of these treatments leads to cartilage regeneration nor permanent improvement of the initial damage. As described previously, some of SF cells also have mesenchymal stem cell (MSC) like properties and important regenerative potential [2][3][4][5][6]. Dogs are the model recommended by the Osteoarthritis Research Society International (OARSI) for investigation of OA pathogenesis [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations